Impact of COVID-19 Pandemic Measures and Restrictions on Cellular Network Traffic in Malaysia - Murad S.S.; Yussof S.; Badeel R.; Ahmed R.A. (Science and Information Organization, 2023)
Locks (fasteners); Mobile telecommunication systems; Network performance; Wireless networks; Case-studies; Cellular network; Cellular network traffics; Covid-19; Malaysia; On-line service; Online content; Pandemic; Phone applications; Social distance; COVID-19